Building A Predictive Model for Student Decisions: The Role of Investment Understanding, Herding Behavior and Risk Tolerance - Mulyani, Elis Listiana; Rahmani, Dede Arif; Kurniawan, Dian; Paturochman, Iwan Ridwan; Rinandiyana, Lucky Radi; Badriatin, Tine (Indonesian Journal of Social Science Research, 2024)
Various factors influence the investment decisions of Siliwangi University students, such as their understanding of investment and herding behavior, and risk tolerance. So the problem formulation in this study is about how the effect of investment understanding on student investment decisions in the capital market, how the effect of herding behavior on student investment decisions in the capital market, how the effect of Risk Tolerance on student investment decisions in the capital market, how the effect of investment understanding, herding behavior and Risk Tolerance on student investment decisions in the capital market. While the purpose of this study is to identify and describe the effect of investment understanding on student investment decisions in the capital market, the effect of herding behavior on student investment decisions in the capital market, the effect of risk tolerance on student investment decisions in the capital market, and the combined effect of investment understanding, herding behavior, and risk tolerance on student investment decisions in the capital market. This research uses a descriptive method with a verification approach. The data collection technique was carried out through a questionnaire as primary data. The results of the study will be analyzed using correlation analysis, determination, and F test.